Pyrolysis of Lubricant Waste into Liquid Fuel using Zeolite Catalyst - Heru Afriansyah; M. Reza Ramlan; Miranda Roulina T; Yohandri Bow; Fatria (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
The number of means of transportation in Indonesia continues to increase from year to year. Along with this, the amount of used oil waste oil becomes something more useful by considering the high hydrocarbon content, namely the pyrolysis method with a raw material ratio of 1:1 to be converted into liquid fuel which is ready to be commercialized by catalytic cracking process using a zeolite catalyst of a certain amount. 25% by weight of the raw material which is useful for accelerating the reaction so as to save energy use and improve the quality of the resulting product. Observations were made by looking at the effect of temperature variations ranging from 250oC, 300oC, 350oC, to the results of the pyrolysis process which aims to obtain the optimal process temperature.